2010
DOI: 10.1002/dvg.20672
|View full text |Cite
|
Sign up to set email alerts
|

Brain expression of Cre recombinase driven by pancreas‐specific promoters

Abstract: Summary Cre-loxP technology enables specific examination of the function and development of individual nuclei in the complex brain network. However, for most brain regions, the utilization of this technique has been hindered by the lack of mouse lines with Cre expression restricted to these regions. Here, we identified brain expressions of three transgenic Cre lines previously thought to be pancreas-specific. Cre expression driven by the rat-insulin promoter (Rip-Cre) was found mainly in the arcuate nucleus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 39 publications
5
90
0
Order By: Relevance
“…The transgenic expression in RIP-I/Reg3␤ mice was specific, as other tissues (duodenum, cerebellum, hypothalamus, liver, and muscle) did not show increased Reg3␤ mRNA level using real-time PCR vs. wild-type counterparts (data not shown). This was in agreement with the findings that insulin I gene was specifically expressed in the ␤-cells, unlike the insulin II promoter that directed a significant, ectopic expression in the brain (33,49,58).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The transgenic expression in RIP-I/Reg3␤ mice was specific, as other tissues (duodenum, cerebellum, hypothalamus, liver, and muscle) did not show increased Reg3␤ mRNA level using real-time PCR vs. wild-type counterparts (data not shown). This was in agreement with the findings that insulin I gene was specifically expressed in the ␤-cells, unlike the insulin II promoter that directed a significant, ectopic expression in the brain (33,49,58).…”
Section: Resultssupporting
confidence: 81%
“…A recent evaluation of several strains expressing Cre recombinase and directing conditional gene targeting revealed that the commonly used rat insulin II promoter (668 bp, often marked as RIP) caused ectopic recombination in most brain areas, especially the midbrain and ventral regions, in addition to the islet ␤-cells (11,49,58); Pdx1-Cre also caused an unexpected recombination in a subset of hypothalamic neurons involved in energy and nutrient homeostasis (58). On the other hand, an 8.5-kb mouse insulin I promoter was successfully used to express cGFP and Cre exclusively in the ␤-cells (58).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Because Pdx1-Cre is active in the hypothalamus (36,46,47), a region of the central nervous system critical for metabolic control, we analyzed Foxd3 mRNA expression in the hypothalamus of control animals using RT-PCR and determined that Foxd3 mRNA was not detectable in this region (Supplemental Fig. 1, published Fig.…”
Section: Figmentioning
confidence: 99%
“…However, Oropeza et al (12) provide a more extensive and detailed analysis of this mouse model. First, strong evidence is provided using higher resolution techniques and the mT/mG reporter line (20) that Cre activity is indeed exclusively found in b-cells and not in hypothalamic or hindbrain nuclei, as was reported before in other strains (7,8). Furthermore, whole-body glucose homeostasis was similar to controls, both on normal chow and after a high-fat, high-sucrose (HFHS) diet.…”
mentioning
confidence: 52%
“…There have been reports of disturbed endogenous gene expression at the site of the Cre-transgene insertion (4), low or mosaic Cre expression (5,6), and expression in undesired tissues, such as unwanted Cre activity in nutrient-sensing neurons from transgenic mice that express Cre under the control of Ins2 and Pdx1 promoters (7,8). Equally disturbing is the finding that high Cre activity can cause chromosomal rearrangements, apoptosis, and decreased proliferation (9-11).…”
mentioning
confidence: 99%